The Theology of sungai Deras Community in Kanduhai Sko - Ahmad Zuhdi*; Suci Elmiyanti (The Progress: Journal of Language and Ethnicity, 2022)
This article raises the title " Theology of Sungai Deras  Community in Kanduhai Sko". In the Kerinci community, especially Sungai Deras village, Kanduhai Sko is a tradition that is considered sacred. Many varieties and styles of worship are shown when the Kanduhai event is held. Seeing that there are various religious aspects in the traditional ceremony, makes this topic very interesting to be raised. Because no community is not involved in organizing this sacred event, ranging from children, youth, youth, and parents, who reside and live in Sungai Deras village. The findings in this study indicate the divine values ​​at the Kenduri Sko event for the Sungai Deras community.